Application of GESCA in Consumer Satisfaction Antecedents to Create Brand Love Local Products in Ambon City - Walter Tabelessy (PT FORMOSA CENDEKIA GLOBAL, 2023)
The existence of competition between Roti Galala as one of the pioneers of local bread products with other bread products has an impact on decreasing consumer satisfaction which also has an impact on the formation of consumer brand love for Roti Galala products. So the purpose of this study is to analyze the effect of product quality, price fairness, brand experience and brand image on customer satisfaction to foster brand love for local Roti Galala products in Ambon City. To achieve the research objectives, a convenience sampling technique was used using a questionnaire distributed directly to 251 consumers who consume Roti Galala in Ambon City. The GESCA analysis technique was used to test the hypothesis in this study using the GESCA version 1.5 Web application. The results of data processing show that the model in the study is fit and accepts all the hypotheses proposed, namely product quality has a positive and significant effect on customer satisfaction, price fairness has a positive and significant effect on customer satisfaction, brand experience has a positive and significant effect on customer satisfaction, brand image has a positive and significant effect on customer satisfaction, and customer satisfaction has a positive and significant effect on brand love